Thanadelther (ca. 1700-1717) - Smith, James G.E. (ARCTIC, 1984)
The Thanadelther of Chipewyan legend was one of the most important and enduring figures of northwestern Canada and perhaps the only woman to play a truly significant part in its early history. . Serving as a guide and interpreter, she led employees of the Hudson's Bay Company to their first meeting with the Chipewyan in the Indians' home territory. As well, she was instrumental in establishing peace between the Cree and their traditional enemies, the Chipewyan, an absolute requisite before the Chipewyan could be brought into the trade with the Company. . Thanadelther's story, as it is recited by Chipewyan elders, is remarkably similar to that recorded by Captain Knight in the daily post journal of York Fort in the period 1715-1717. . In a society in which the status of women was extraordinarily low, the Slave Woman was the leader and the strength of the journey across the Barrens, the forceful orator, the one of indomitable courage [who forged ahead on her own to bring reconciliation between the Cree and Chipewyan]. Both Knight and Stewart recognized that the success of the mission was due to her as "the Chief promoter and Acter of it". On the day of her death, Knight wrote: "She was one of a Very high Spirit and of the Firmest Resolution that ever I see any Body in my Days and of great Courage & forecast."